2022
DOI: 10.3341/kjo.2022.0012
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Lacrimal Gland Extraction on the Contralateral Eye in an Animal Model for Dry Eye Disease

Abstract: Purpose: Although there is still no consensus on the best animal model for dry eye disease research, a model based on lacrimal gland extraction (LGE) model is widely used. In this study, we aimed to investigate the histopathological changes taking place on the contralateral eye after unilateral LGE to determine whether it is useful as a control.Methods: Seven-week-old male C57BL/6 mice were divided into naive control, environmental chamber model, and LGE groups. Corneal fluorescein staining was scored to quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…They are in accordance with previous descriptions of regional and systemic repercussions of LG losses in mice. A recent study observed the response to LG complete ablation in mice and reported changes on the contralateral side, including inflammation of the LG, keratitis, and reduction in conjunctival goblet cells [35]. Another study with LG complete ablation in mice induced an increase of IL-1β, TNF-α, and MMP-9 mRNA in the ipsilateral cornea [28].…”
Section: Discussionmentioning
confidence: 99%
“…They are in accordance with previous descriptions of regional and systemic repercussions of LG losses in mice. A recent study observed the response to LG complete ablation in mice and reported changes on the contralateral side, including inflammation of the LG, keratitis, and reduction in conjunctival goblet cells [35]. Another study with LG complete ablation in mice induced an increase of IL-1β, TNF-α, and MMP-9 mRNA in the ipsilateral cornea [28].…”
Section: Discussionmentioning
confidence: 99%